2015
DOI: 10.1128/aem.02037-15
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Vertical Transmission of Bifidobacteria from Mother to Child

Abstract: Passage through the birth canal and consequent exposure to the mother's microbiota is considered to represent the initiating event for microbial colonization of the gastrointestinal tract of the newborn. However, a precise evaluation of such suspected vertical microbiota transmission has yet to be performed. Here, we evaluated the microbiomes of four sample sets, each consisting of a mother's fecal and milk samples and the corresponding infant's fecal sample, by means of amplicon-based profiling supported by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
206
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 212 publications
(237 citation statements)
references
References 45 publications
23
206
0
8
Order By: Relevance
“…Current studies indicate that bifidobacteria are transmitted vertically from the mother's vagina, GI tract, or breast milk. This is supported by findings by Duranti et al [22], who used a novel internal transcribed spacer (ITS) approach trialled previously [23]. Duranti et al found genomically identical bifidobacteria strains in faecal and milk samples from 24 mother-infant pairs.…”
Section: Bifidobacterium Across the Life Coursesupporting
confidence: 70%
“…Current studies indicate that bifidobacteria are transmitted vertically from the mother's vagina, GI tract, or breast milk. This is supported by findings by Duranti et al [22], who used a novel internal transcribed spacer (ITS) approach trialled previously [23]. Duranti et al found genomically identical bifidobacteria strains in faecal and milk samples from 24 mother-infant pairs.…”
Section: Bifidobacterium Across the Life Coursesupporting
confidence: 70%
“…It will be similarly crucial to associate the presence of strains or subclades of microbial species with immune or chronic disease phenotypes even in the absence of acute infection. The same types of approaches can also start to unravel how members of the microbiome without overt phenotypes are transmitted among hosts, e.g., in vertical mother-to-infant transmission (Milani et al 2015;Asnicar et al 2017) or horizontal orofecal routes . This is of particular interest in the context of interventions such as probiotics or fecal microbiome transplants, in which strain tracking is necessary to identify successful receipt or engraftment of the intended microbes (Li et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Only very recently, a study based on analysis of the gut microbiota of mothers and corresponding children by a combination of amplicon-based profiling and shotgun metagenomics demonstrated that mother and child share particular bifidobacterial strains, belonging to Bifidobacterium breve and Bifidobacterium longum subsp. longum, which is thus indicative of vertical transmission (11,12). Mode of delivery (i.e., vaginally delivered versus delivered by cesarean section) and type of nutrition (i.e., breast-fed versus bottle-fed) are considered to be important factors that provide differential colonization opportunities, thereby impacting the composition of the neonatal gut microbiota, including the colonization level and species composition of bifidobacteria (13,14).…”
mentioning
confidence: 99%